Caccia‘s art: Cyrus’s leadership in Niccolò Machiavelli - Mattei, Eugenia (Estudios de Filosofía, 2015)
The main aim of this article is to analyze the figure of Cyrus in Niccolò Machiavelli’s work. For this purpose, we will provide a systematization of mentions of Cyrus in Machiavelli’s work –Discorsi and Il Principe-, so as to later tackle the specific uses Machiavelli gives to this figure based on his own queries. From that point, a series of assertions are derived about the relationship between the leader and the people, which are useful to delve into the Machiavellian undertaking.